Phytochemical Screening of Noni (Morinda citrifolia L) Leaf Ethanol Extract in Pejagan Village, Bangkalan Regency - Fitroh Annisaul Mubarokah; Winda Yuliasari; Teguh Setiawan Wibowo (PT FORMOSA CENDEKIA GLOBAL, 2023)
Indonesia has a very high amount of biodiversity. This is evidenced by the many types of medicinal plants that grow in this country. Noni fruit is one of the most popular medicinal plants in Indonesia and has high efficacy. However, the utilization of noni leaves is still not maximal. This study aimed to test for the presence of secondary metabolites in the ethanol extract of noni leaves using phytochemical screening. The results showed that the ethanol extract of noni leaves from Pejagan village positively contained alkaloids, terpenoids, steroids, flavonoids, tannins, and saponins.